Diagnosis And Surgical Management Of Urethrolith In A Dog - Kumar, Dinesh; Behl, S.M.; singh, Prem; Tayal, Rishi; Pal, Madan; Chandolia , R.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Diseases of the urethra frequently result in partial or complete obstruction of the flow of urine in dogs. This obstruction results in uremia within 2 to 3 days and death within 3-6 days ( Kalhr, 1983). Ischial arch and posterior of os-penis are common sites of lodging the urethral calculi (Burk and Ackerman, 1996). Both these sites are difficult to visualise ultrasonographically (Kundu and Ghosh, 2006). The lumen of urethra remains collapsed except at the time of micturition. This is the reason along with os-penis for poor ultrasonographic visualisation of urethra. The calculi from urinary bladder may also get lodged in the urethra during voiding out. These urethroliths causes obstruction of urine and inflammation of urethra. Cystotomy is a common surgical procedure in small animal veterinary practice, typically performed to remove cystic calculi (Cornell, 2000).